Concomitant Use of Panobinostat and Reirradiation in Progressive DIPG: Report of 2 Cases. Issue 6 (August 2017) - Wang, Zhihong J.; Ge, Yubin; Altinok, Deniz; Poulik, Janet; Sood, Sandeep; Taub, Jeffrey W.; Edwards, Holly; Kieran, Mark W.; Steven, Miller
Abstract : Diffuse intrinsic pontine glioma (DIPG) remains a devastating disease. Panobinostat has been shown to have therapeutic efficacy both in vitro and in DIPG orthotopic xenograft models; however, clinical data in patients with DIPG are lacking. We present 2 cases of DIPG, who were treated with panobinostat at 22 to 25 mg/m 2 /dose, 3 times weekly for 2 weeks in 3-week cycles and concomitant reirradiation after disease progression. Two episodes of asymptomatic thrombocytopenia were observed in 1 patient. Hyperacetylation of histone H4 of peripheral blood mononuclear cells was evident following treatment. In our experience, panobinostat administered with reirradiation was well tolerated at a relatively higher dose than that used in adult studies.